Basic fibroblast growth factor promotes melanocyte migration via activating PI3K/Akt‐Rac1‐FAK‐JNK and ERK signaling pathways. Issue 9 (27th June 2016) - Shi, Hongxue; Lin, Beibei; Huang, Yan; Wu, Jiang; Zhang, Hongyu; Lin, Cai; Wang, Zhouguang; Zhu, Jingjing; Zhao, Yingzhen; Fu, Xiaobing; Lou, Zhencai; Li, Xiaokun; et al.
Abstract: Vitiligo is a depigmentation disorder characterized by loss of functional melanocytes of the skin epidermis. The pathogenesis of vitiligo remains elusive. The purpose of this study is to investigate the effects of basic fibroblast growth factor (bFGF) on melanocyte migration, including its biochemical mechanism using transwell assay in vitro. We found that melanocyte treated with bFGF showed a significant increase in migration and cytoskeletal rearrangement. These changes were associated with increased activation of PI3K/Akt, Rac1, FAK, JNK, and ERK. Likewise, reduction of PI3K/Akt, Rac1, FAK, JNK, and ERK activity using selective inhibitors or siRNA was associated with impediment of bFGF‐induced melanocyte migration. In addition, activity of Rac1, FAK, and JNK was reduced in cells in which PI3K/Akt was inhibited, activity of FAK and JNK was reduced in cells in which the Rac1 was inhibited, and activity of JNK was reduced in cells in which the FAK was inhibited. Collectively, these data demonstrate that bFGF facilitated melanocyte migration via PI3K/Akt‐Rac1‐FAK‐JNK and ERK signaling pathways. © 2016 IUBMB Life, 68(9):735–747, 2016